Endoscopic sleeve gastroplasty with argon plasma coagulation: A novel technique. Issue 11 (15th November 2020) - Itani, Mohamad I.; Farha, Jad; Sartoretto, Adrian; Abbarh, Shahem; Badurdeen, Dilhana; de Moura, Diogo T. H.; Kumbhari, Vivek
Abstract : Objective: The endoscopic sleeve gastroplasty (ESG) is a minimally invasive procedure in which the anterior and posterior aspects of the greater curvature are stitched endoscopically, producing a sleeve‐like anatomy mimicking that in a sleeve gastrectomy. However, suture dehiscence and enlargement of the stomach within months of the procedure have been observed. Argon plasma coagulation (APC) is widely used in gastrointestinal endoscopy and is able to induce scarring and fibrosis. We coupled ESG with APC to evaluate its potential to improve durability. Methods: A 46‐year‐old woman with obesity presented for ESG. Her pre‐procedure weight was 117 kg with a body mass index (BMI) of 41.4 kg/m 2 . After each plication was complete, APC (60 W, argon flow rate 1.2 L/min) was used to ablate the mucosal surface of the exposed plicated mucosa. APC was applied until the mucosal color was dark brown, indicating adequate and successful mucosal and submucosal ablation. Results: The procedure was successful, and the patient recovered without peri‐ or post‐operative complications. The procedure time was 47 minutes. A total of seven sutures were used. At 6‐month follow‐up the patient had lost 17 kg (37.5 lbs), equivalent to 14.5% total weight loss and had a BMI of 35.4 kg/m 2 . Endoscopic follow‐up at 6 months revealed enhanced fibrosis along the plications, resulting in a superior, sleeve‐like lumen. Conclusions: The combination of ESG with APC may act synergistically to reduce weight without adding significant procedure time. Further investigation is needed to determine whether it should be widely recommended. Abstract : The endoscopic sleeve gastroplasty (ESG) is a minimally invasive procedure in which the gastric lumen is stitched endoscopically. Argon plasma coagulation (APC) is a separate, multipurpose tool that is widely used in gastrointestinal endoscopy. The combination of ESG and APC may act in a synergistic manner to reduce weight without adding significant procedure time.